2019
DOI: 10.1038/s41598-019-48433-5
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of the sulfur amino acid biosynthetic pathway in Cryptococcus neoformans: the relationship of Cys3, Calcineurin, and Gpp2 phosphatases

Abstract: Cryptococcosis is a fungal disease caused by C . neoformans . To adapt and survive in diverse ecological niches, including the animal host, this opportunistic pathogen relies on its ability to uptake nutrients, such as carbon, nitrogen, iron, phosphate, sulfur, and amino acids. Genetic circuits play a role in the response to environmental changes, modulating gene expression and adjusting the microbial metabolism to the nutrients available for the best energy usage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 94 publications
4
32
0
Order By: Relevance
“…Calcineurin has been linked to osmotic stress and cell wall integrity response in C. neoformans (Kraus and Heitman, 2003; Fan et al, 2007). Also, the relationship between calcineurin complex and GPP2 identified in our previous work and others reinforces the idea that this phosphatase complex plays an important role on osmobalance (Park et al, 2016; Jung et al, 2018; de Melo et al, 2019).…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…Calcineurin has been linked to osmotic stress and cell wall integrity response in C. neoformans (Kraus and Heitman, 2003; Fan et al, 2007). Also, the relationship between calcineurin complex and GPP2 identified in our previous work and others reinforces the idea that this phosphatase complex plays an important role on osmobalance (Park et al, 2016; Jung et al, 2018; de Melo et al, 2019).…”
Section: Introductionsupporting
confidence: 87%
“…Interruptions on amino acid biosynthesis or failure to uptake amino acids by permeases lead to growth arrest, defects in virulence factor and decreased virulence in mouse and Galleria mellonella animal model of infection (Yang et al, 2002; Pascon et al, 2004; Fernandes et al, 2015; Martho et al, 2016; Calvete et al, 2019). Recently, we showed the regulation of sulfur amino acid biosynthesis is essential for C. neoformans survival in vivo and in vitro (de Melo et al, 2019). Cys3 transcription factor, the major regulator of the sulfur uptake network, is part of a protein complex and physically interacts with calcineurin and Gpp2 phosphatase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peptides were eluted on a capillary analytical column (C18 nanoAcquity BEH 75 μm x 150 mm, 1.7 μm column) using a gradient of 93% A (0.1% formic acid) and 7% B (99.9% ACN 0.1% formic acid) to 35% B over 30 min in a flow of 275 nl / min. Data were acquired in MS E mode [32,33] in duplicate. Protein identification, PTM and homology searches were performed in PEAKS Studio 7.5 software (Bioinformatics Solutions Inc.) by MS/MS search against the Serpentes databases obtained from Uniprot (2844 sequences, downloaded in October 25 th , 2018).…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…Similarly to MET3 and MET6, MET2 is also necessary for Met biosynthesis in C. neoformans and disruption of this gene leads to Met auxotrophy and avirulence (Nazi et al, 2007). Further, it has been revealed that CYS3 encodes a transcriptional activator that upon deletion causes a Met/Cys auxotrophy and that Cys3 is the major regulator of inorganic sulfur uptake in C. neoformans (de Melo et al, 2019).…”
Section: Biosynthesis Of Sulfur-containing Amino Acids and Metabolitesmentioning
confidence: 99%